Analisis Tingkat Keramah Lingkungan Alat Tangkap Bubu Naga di TPI Desa Muara Kecamatan Cilamaya Wetan Kabupaten Karawang - Raden Muhamad Abdul Rohman Gani; M. Tajuddin Noor; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Dragon trap is a passive trap that is operated by utilizing the ebb and flow of waters. The purpose of this study was to determine the level of environmental friendliness of the dragon trap fishing gear in Muara Village, Cilamaya Wetan District, Karawang Regency based on 9 criteria. The research method used a questionnaire based on 9 criteria in the CCRF (Code of Conduct for responsible fisheries).